2017
DOI: 10.5005/jp-journals-10024-2108
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Variants of Calcifying Odontogenic Cyst: A Study of 52 Cases

Abstract: Aim: This study aimed at evaluating histological features of 52 cases of calcifying odontogenic cyst (COC), which is an uncommon benign odontogenic lesion. The World Health Organization (WHO) classified COC as a neoplasm and used the term calcifying cystic odontogenic tumor (CCOT) for benign cystic type and the dentinogenic ghost cell tumor (DGCT) for the benign solid-type lesions. There is no agreement regarding COC classification. Materials and methods:A total of 52 cases of COC were selected and reviewed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…In the present survey, the mean age of individuals with COC, DGCT, and GCOC was 30.7, 47.0, and 42.6 years, respectively, in agreement with findings of large case series reported elsewhere . Corroborating data of Ledesma‐Montes et al, Irani & Foroughi, Cheng et al, and Etemad‐Moghadam et al, men seem to be more affected.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present survey, the mean age of individuals with COC, DGCT, and GCOC was 30.7, 47.0, and 42.6 years, respectively, in agreement with findings of large case series reported elsewhere . Corroborating data of Ledesma‐Montes et al, Irani & Foroughi, Cheng et al, and Etemad‐Moghadam et al, men seem to be more affected.…”
Section: Discussionsupporting
confidence: 92%
“…Root resorption or root displacement and cortical erosion could be observed. Root displacement or root resorption may also be absent . DGCT cases were found to have a well‐defined (66.7%) unilocular border (51.8%) with mixed appearance (60.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Although some previous reports have not shown a gender preference of COC (Gomes da Silva et al., ; Lucchese et al., ; Shamaskin et al., ), others have demonstrated a male prevalence (Irani & Foroughi, ; Ledesma‐Montes et al., ). In our multicentre study, there was a slight female prevalence (female‐to‐male ratio: 1.2:1), diverging from the present literature review that showed 247 males (56.2%) among the 439 informed cases (male‐to‐female ratio: 1.2:1).…”
Section: Discussionmentioning
confidence: 91%
“…In this Brazilian survey, COC represented 0.1% of cases among the entire sample of diagnosed oral and maxillofacial lesions and 1.3% of cases among all odontogenic cysts. Two single‐centre studies from Iran (Habibi, Saghravanian, Salehinejad, & Jafarzadeh, ; Irani & Foroughi, ) and an international collaborative study involving 14 institutions of Europe, Africa and America (Ledesma‐Montes et al., ) also provided a large case series of this lesion. The strength of our study regards the report of the frequency of COC identified across 10 reference services in a multicentre collaboration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation